Supporting the management of a company informatics infrastructure with applications offered in the form of e-services - Dziembek, Damian (Wspomaganie zarządzania infrastrukturą informatyczną przedsiębiorstwa aplikacjami oferowanymi w formie e-usług, 2011)
The paper presents a model of managing a company informatics infrastructure with the help of applications available in SaaS form. The introductory section briefly discusses the problematics of informatics infrastructure management in companies. Then, SaaS model is discussed as a form of an e-service which provides remote access to software. Main advantagesand drawbacks connected with this form of utilizing applications are pointed out. Thefinal part of the paper contains a list of domestic and foreign applications available in SaaSform, which might be found useful in supporting the management of informatics infrastructure in companies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 109-122
Keywords: SaaS model; informatics infrastructure management